Confirmation of a new phenotype in an individual with a variant in the last part of exon 30 of CREBBP. Issue 4 (8th February 2019) - Angius, Andrea; Uva, Paolo; Oppo, Manuela; Persico, Ivana; Onano, Stefano; Olla, Stefania; Pes, Valentina; Perria, Chiara; Cuccuru, Gianmauro; Atzeni, Rossano; Serra, Gigliola; Cucca, Francesco; et al.
Abstract : We report here a novel de novo missense variant affecting the last amino acid of exon 30 of CREBBP [NM_004380, c.5170G>A; p.(Glu1724Lys)] in a 17‐year‐old boy presenting mild intellectual disability and dysmorphisms but not resembling the phenotype of classical Rubinstein–Taybi syndrome. The patient showed a marked overweight from early infancy on and had cortical heterotopias. Recently, 22 individuals have been reported with missense mutations in the last part of exon 30 and the beginning of exon 31 of CREBBP, showing this new phenotype. This additional case further delineates the genotype–phenotype correlations within the molecular and phenotypic spectrum of variants in CREBBP and EP300 .